A review of computational approaches to predict gene functions - Swee Kuan Loh; Swee Thing Low; Lian En Chai; Weng Howe Chan; Mohd Saberi Mohamad; Safaai Deris; Zuwairie Ibrahim; Shahreen Kasim; Zuraini Ali Shah; Hamimah Mohd Jamil; Zalmiyah Zakaria; Suhaimi Napis (Bentham Science Publishers, 2018)
Recently, novel high-throughput biotechnologies have provided rich data about different genomes. However, manual annotation of gene function is time consuming. It is also very expensive and infeasible for the growing amounts of data. At present there are numerous functions in certain species that remain unknown or only partially known. Hence, the use of computational approaches to predicting gene function is becoming widespread. Computational approaches are time saving and less costly. Prediction analysis provided can be used in hypotheses to drive the biological validation of gene function.